Thriving in the Automated Economy. - Brynjolfsson, Erik; McAfee, Andrew (Futurist)
The article discusses the impact of technologies on the well-being of workers and their societies. It argues that, although the Industrial Revolution coincided with increasing numbers of jobs, there is no law of economics that states that that will always be true. As remedies to possible unemployment, the authors recommend finding ways for workers to partner with technologies, cultivating creative entrepreneurship, and investing in human capital. They offer a plan for the U.S. economy that involves education reforms, investment in research and infrastructure, and removal of regulations that are said to inhibit innovation.